Avaliação do conhecimento de professores de educação infantil sobre saúde bucal - Andrade, Cristiane Mendes de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The school setting has been considered a suitable location for the development of health programs, because it gathers children of age favorable to the adoption of educational and preventive measures. It is known that teachers act as an educator in shaping the opinions and information assimilation, and that education is main instrument on the prevention of dental cavities. Thus the objective of this study was to identify the knowledge of early childhood educators on oral health in state and municipal schools. It was taken into account the total number of teachers who taught at four preschools during 2010 academic year in the city of Araçatuba SP, chosen randomly, in a total of 20 teachers. The group of teachers who joined the research was organized based on two criteria: having a bachelor degree and the agreement to participate. It is a descriptive study of transversal character. For collection of data, a semistructured questionnaire, self-administered, consisting of open and closed questions over the subject was used. They were typed and analyzed by the program Epi Info 3.5.1. .For qualitative analysis, content analysis was used, through the categories analysis technique. Among the results, it is brought to attention that 94.5% reported to work in schools that provide activities in oral health education. The vast majority of 85% claimed to have received information about the care needed to maintain oral health being that 55% recognized dentists as the main source of information, 95% claimed to know what bacterial plaque is, and 25% associated within the bacteria category. On the etiology of dental cavities 65% of teachers attributed its emergence due to poor oral hygiene. With regards to the function of fluoride in relation to dental cavities 90% indicated knowledge over it. Of these, 35% attributed as the function of protecting...

A escola tem sido considerada um local adequado para o desenvolvimento de programas de saúde por reunir crianças em faixas etárias propícias à adoção de medidas educativas e preventivas. Sabe-se que os professores atuam como educadores na formação de opiniões e na assimilação de informações, e que a educação é o principal instrumento para prevenção da cárie dental. Deste modo o objetivo do presente estudo foi identificar o conhecimento de professores de educação infantil de escolas estaduais e municipais sobre saúde bucal. Para a coleta dos dados utilizou-se um questionário semiestruturado, auto-aplicável, composto por questões abertas e fechadas sobre o tema. Os mesmos foram digitados e analisados pelo programa Epi Info, 3.5.1. Entre os resultados obtidos pode-se observar que 94,5% relataram atuar em escolas que possuem atividades de educação em saúde bucal. A grande maioria 85,% afirmou ter recebido informações a respeito dos cuidados necessários para a manutenção da saúde bucal sendo que 55% atribuem ao cirurgião dentista à principal fonte dessa informação, 95% afirmaram saber o que é placa bacteriana destes 25% associaram-na a categoria bactérias. Sobre a etiologia da cárie dentária 65% dos professores condicionaram seu aparecimento a má higiene bucal. No que se refere à função do flúor em relação à cárie dentária 90% indicaram conhecê-la. Destes, 35% atribuíram ao mesmo a função de proteção da estrutura dental e 55% citaram as águas de abastecimento público como o local onde o mesmo pode ser encontrado. Podese concluir que os professores possuem pouco conhecimento a respeito da saúde bucal, necessitando de maiores informações para abordarem estes temas em sala de aula com maior segurança
Keywords: Professores; Pre-escolares; Educação em saúde; Saúde bucal; Oral health